2012
DOI: 10.3168/jds.2011-4583
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma insulin concentration to fatty acid distribution between milk fat and membrane synthesis

Abstract: We examined the association between plasma insulin concentration and fatty acid distribution to milk fat and membrane fractions (triglyceride and phospholipid, respectively) in dairy cows. Thirty-seven Holstein cows at 60 to 70 d postpartum were synchronized by 2 PGF(2α) injections 14 d apart. Plasma samples were taken before morning and evening milkings and milk samples were obtained at morning milking. Plasma insulin concentrations were determined and cows were retrospectively assigned to low insulin (LI; 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…However, an association has been found between the composition of some milk constituents and mean diameter of the MFG. For example, MFG size is closely associated with its membrane's PL (Argov et al, 2008;Lopez, Medac, & Jimenez-Flores, 2010;Mesilati-Stahy & Argov-Argaman, 2014;Mesilati-Stahy et al, 2011) and fatty acid composition (Briard, Leconte, Michel, & Michalski, 2003;Couvreur, Hurtaud, Marnet, Faverdin, & Peyraud, 2007;Lopez et al, 2008;Mesilati-Stahy, Malka, & Argov-Argaman, 2012;Mesilati-Stahy et al, 2011;Michalski et al, 2006;O'Mahony, Auty, & McSweeney, 2005). Several studies have reported a positive correlation between MFG mean diameter and milk total lipid content (Couvreur et al, 2007;Menard et al, 2010) or with diurnal fat yield (Wiking, Stagsted, Bjorck, & Nielsen, 2004), while others found no positive correlation between fat content and MFG size (King, 1957;Walstra, 1969).…”
Section: Introductionmentioning
confidence: 90%
“…However, an association has been found between the composition of some milk constituents and mean diameter of the MFG. For example, MFG size is closely associated with its membrane's PL (Argov et al, 2008;Lopez, Medac, & Jimenez-Flores, 2010;Mesilati-Stahy & Argov-Argaman, 2014;Mesilati-Stahy et al, 2011) and fatty acid composition (Briard, Leconte, Michel, & Michalski, 2003;Couvreur, Hurtaud, Marnet, Faverdin, & Peyraud, 2007;Lopez et al, 2008;Mesilati-Stahy, Malka, & Argov-Argaman, 2012;Mesilati-Stahy et al, 2011;Michalski et al, 2006;O'Mahony, Auty, & McSweeney, 2005). Several studies have reported a positive correlation between MFG mean diameter and milk total lipid content (Couvreur et al, 2007;Menard et al, 2010) or with diurnal fat yield (Wiking, Stagsted, Bjorck, & Nielsen, 2004), while others found no positive correlation between fat content and MFG size (King, 1957;Walstra, 1969).…”
Section: Introductionmentioning
confidence: 90%
“…Total lipids were extracted from 0.5 mL milk with 10 mL chloroform-methanol (2∶1, vol/vol) as described previously [21]. For the HPLC analysis, 100 µL chloroform–ethanol (97∶3 vol/vol) was added to the evaporated tubes containing lipids and stored at -20°C until injection into the HPLC.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a strong association between milk fat content and MFG size has been demonstrated in dairy cows [18], by diet-induced alterations in milk fat content [13], and by interspecies comparison of milk fat concentrations [19]. Milk fat content has also been associated with the composition of PL in MFG of dairy goats and cows [20], [21]. Furthermore, association between TAG and PL composition [12], [13], [14], [22] and MFG size has been illustrated in human as well as bovine milk.…”
Section: Introductionmentioning
confidence: 99%
“…Other parameters that have been shown to modulate milk fat content and MFG size are lactation stage (Mesilati-Stahy and Argov-Argaman, 2014) and genetic disposition (Couvreur et al, 2007;Argov-Argaman et al, 2013). Interestingly, conditions that induce changes in MFG mean diameter also change milk PL content and composition (Lopez et al, 2008;Mesilati-Stahy et al, 2012), suggesting a link between the metabolic pathways regulating the composition of the mammary gland cell membranes and MFG size. The effect of altered composition of MFGM on MFG size is still unclear, although in other cell models, regulation of intracellular lipid droplet size through altered membrane composition has been demonstrated (reviewed by Thiam et al, 2013).…”
Section: Elevated Concentrate-to-forage Ratio In Dairy Cow Rations Ismentioning
confidence: 99%
“…Extraction of Total Lipids from Milk and Plasma. Total lipids were extracted from the milk using a protocol adapted from the cold-extraction procedure developed by Folch et al (1957), as previously described (Mesilati-Stahy et al, 2012). Briefly, each sample was extracted twice, once for lipid analysis by normal-phase LC and once for FA analysis by GC.…”
Section: Lipid Extraction From Plasma and Milkmentioning
confidence: 99%